Pemanfaatan Big Data dalam Bisnis E-commerce OLX - Airlangga Maulana H; Citra Adinda Hartawan; Firda Della Irawan; Pramoedya Seta Ananta (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2021)
Basically, the emergence of online sales sites is a positive impact on the development of information technology. Not a few online markets selling similar goods and services. However, there are many considerations between consumers in sorting and choosing what goods they will buy as well as the inventory of goods displayed on the online market. Every online marketplace must compete to increase its sales profit by researching the data entered on the account sites used by consumers. The type of research used is quantitative research. By utilizing advances in technology, the use of data mining is an efficient way to retrieve and collect the required data. Data mining, often also called knowledge discovery in database (KDD), is an activity that includes collecting, using historical data to find regularities, patterns, or relationships in large data sets. The output of this data mining can be used to improve decision-making in the future. So the term pattern recognition is now rarely used because it is part of data mining. Observations are carried out directly on the olx.co.id web by visiting the site, then documenting the site by printing a screen to be able to take pictures of the website display in other words we can compare one product with other products and see how many products there are. sold out. In this study, researchers also explain the flow of product orders using OLX e-commerce. E-commerce platforms also allow businesses to gather a wealth of statistics about how many customers come to their website, how they choose or compare alternatives, and what the logic is in each buying situation.